GUNSLINGER GIRL - ELY, LYNDSAY (New York : Jimmy Patterson Books / Little, Brown and Company, 2018)
Seventeen-year-old Serendipity "Pity" Jones inherited two things from her mother: a pair of six shooters and perfect aim. When her father attempts to marry her off to a stranger, she runs away from their humble farming commune and ends up in the most dangerous, decadent city on the continent: Cessation (a lawless Las Vegas). Pity becomes the star of the Theater Vespertine as a trick sharpshooter like Annie Oakley, and there she finds fame, friendship and -- what she most wanted -- belonging. But there's a darker side to the Theater... The Finale. Every so often the fighting factions of Cessation have to be kept in line with a little demonstration, a nightmarish public execution. And Pity has a starring role...
Keywords: English fiction